2014
DOI: 10.11607/ijp.3815
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of a Selection of Full-Contour All-Ceramic Crowns: An In Vitro Study

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 0 publications
2
40
0
3
Order By: Relevance
“…For resin-based materials with low modulus of elasticity a recent clinical study found high numbers of debonding between resin nano ceramic crowns and zirconia abutments, which were supposed to be a result of stress concentrations in the adhesive layer [22]. In the present study, LiS, the material with the highest flexural strength and modulus of elasticity, showed the highest fracture resistance, which can be confirmed by the results of previous studies [3,23]. Higher flexural strength of crystallized ZLS (370 MPa) compared to polished ZLS (210 MPa) was reflected in higher fracture forces in two situations (CHAIR, TOOTH).…”
Section: Discussionsupporting
confidence: 90%
“…For resin-based materials with low modulus of elasticity a recent clinical study found high numbers of debonding between resin nano ceramic crowns and zirconia abutments, which were supposed to be a result of stress concentrations in the adhesive layer [22]. In the present study, LiS, the material with the highest flexural strength and modulus of elasticity, showed the highest fracture resistance, which can be confirmed by the results of previous studies [3,23]. Higher flexural strength of crystallized ZLS (370 MPa) compared to polished ZLS (210 MPa) was reflected in higher fracture forces in two situations (CHAIR, TOOTH).…”
Section: Discussionsupporting
confidence: 90%
“…Full-contour polished or glazed zirconia FDPs might be an alternative to veneered restorations because of their high resistance to failure and fracture. Zesewitz et al [40] used single monolithic zirconia crown (MZC), monolithic lithium disilicate and monolithic feldspar ceramic in their study. Monolithic zirconia showed the highest fracture resistance of all the samples studied under axial loading.…”
Section: Fracture Resistancementioning
confidence: 99%
“…The use of translucent zirconia could make it possible to fabricate very strong crowns or fixed dental prostheses using zirconia alone, with no need for a layer of porcelain. It has been reported that full contour zirconia crowns fabricated using such a translucent zirconia are more resistant to fracture than full contour glass ceramic crowns 5,6) and produce less wear on the opposing dentition 7,8) . Most of the zirconia materials currently used in dentistry are partially-stabilized zirconia containing yttria (Y-TZP).…”
Section: Introductionmentioning
confidence: 99%